The Philosophy of Hope: A Christian Approach to Existential Questions - Wulan Retno Sari; Pathus Surur; Bilman Permana (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2024)
This article investigates the concept of hope as a central theme in Christian philosophy, drawing from biblical texts and philosophical works by Søren Kierkegaard and Gabriel Marcel. It examines hope's role in addressing existential crises, suffering, and the search for meaning, contrasting Christian hope with secular existentialism.